THE STUDY OF LONGEVITY: RECENT UPDATES AND FURTHER DIRECTION. PART 1 - Yu. V. Kotovskaya; О. N. Tkacheva; N. К. Runikhina; D. A. Kashtanova; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2017)
The increase  of life duration leads to a sharp growth of the older and senile persons number. Differences in chronological and biological ages, of the velocity of ageing in different persons, make it to study biological and genetic factors of longevity. In the series of reviews we summarize the results of studies in these  areas.  However, except the fundamental scientific interest, general ageing of population and longevity are related to medical and social issues on the geriatric care organization. Regardless  the  high interest,  longevity is still underinvestigated.  The review focuses on the wide spectrum of longevity issues — from genetics to medical and social problems.